Efek Digitalisasi terhadap Praktik dan Kualitas Audit - Ersyafdi, Ilham Ramadhan; Nasution, Cahya Dibah Al-Adawiyah (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
Digitalization has become a major driver in business and organizational transformation in the contemporary era. One area that is significantly affected is audit. This study aims to explain the effects of digitalization on audit practice and quality using libraries or qualitative literature study methods using related journals or scientific articles. This study produces findings that digitalization provides benefits such as efficiency and accuracy which have a positive effect on audit practice and quality. However, there are also challenges such as data security, privacy issues and changing skills paradigms. So, it is very necessary to have a careful strategy in dealing with these changes to ensure the sustainability and effectiveness of audit practices in the future. It is hoped that audit practices can exploit the positive potential of digitalization while overcoming existing challenges. As technology and the business environment continue to change, these efforts will ensure that audit practices remain relevant, effective, and competitive in the ever-evolving digital era.